Research And Design Of Education Management System Based On Cloud Storage - Zhang Yu (P3I UMSurabaya, 2024)
The research and design of education management system based on cloud storage is a process involving the analysis, planning and design of new products or services. Software that helps manage data in cloud storage. It uses asp Net technology, which helps to create an entire application for managing data in cloud storage. The main purpose of this application is to help users store their data, share them with others, and provide them with various functions, such as sharing files, uploading videos, etc. Teaching data is growing exponentially, which brings great storage pressure to traditional data centers. All users share a resource pool, which leads to low efficiency of resource search. Moreover, due to the unclear role and authority of users, teaching resources are safely shared among university users.